Thermal Inactivation of Hepatitis E Virus: A Narrative Review - Tatsuo Kanda; Hiroaki Okamoto (Viruses)
Hepatitis E virus (HEV) infection is an emerging infectious disease. HEV-1 and HEV-2 infect humans through contaminated water and foods, mainly in developing countries. HEV-3 and HEV-4 also infect humans through contaminated food and are thought to be zoonotic infections occurring in both developing and developed countries. A vaccine for hepatitis E is licensed in only limited countries. The inactivation of infectious HEV is very important to ensure the safety of drinking water and foods. HEV-3 and HEV-4 RNA have been detected in some pig liver products, and it is possible that these foods may represent an infectious source of HEV. In this article, previous publications on the heat inactivation and heat stability of HEV are collected, and we discuss the present assessment of the heat inactivation of HEV. The thermal stability of HEV infection in cell culture systems and pig bioassays has been demonstrated, while the efficacy of the method of thermal inactivation using plasma products has not yet been established. Here, we propose that the treatment of HEV-contaminated foods at 95 °C for 10 min is one of the safest options for the inactivation of HEV.